Discourse and long-term effects of isolated and combined structured input and structured output on the acquisition of the English causative form. Issue 2 (3rd April 2019) - Benati, Alessandro; Batziou, Maria
Abstract: The present study explores discourse and long-term effects of structured input (SI) and structured output when delivered in isolation or in combination on the acquisition of the English causative. Research investigating the effects of SI has indicated that it is the causative variable in the positive effects of processing instruction. To provide answers to the questions formulated in this study, one classroom experiment was carried out. Sixty-eight school-age Greek learners (aged 10–12) participated. The participants were randomly assigned to three groups: SI only group ( n  = 22); structured output only group ( n  = 22); combined SI and structured output group ( n  = 24). Subjects who scored lower than 50% in the pre-tests were included in the final data collection. Instruction lasted for 3 h. The design included a delayed post-tests battery (immediate, 3 weeks after instruction, 24 weeks after instruction). The assessment tasks included an interpretation and production task at discourse-level. The results indicated that learners who received SI both in isolation and in combination benefitted more than learners receiving structured output only. These two groups were able to retain instructional gains 3 weeks after instruction (short-term effects) in all assessment measures. Long-term effects after 6 months were also investigated.